2006
DOI: 10.1136/pgmj.2005.039453
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ageing on smell and taste

Abstract: Disorders of taste and smell commonly present diagnostic dilemmas to the medical profession. This may be secondary to the lack of knowledge and understanding of these conditions. There seems to be a low level of interest in the disorders, when compared with disruption of the other senses such as sight and hearing. Nevertheless, impairment of these senses are common and may be life threatening, especially when they involve the elderly patient. The aetiology of the conditions is widespread, and extend beyond the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
136
0
8

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 239 publications
(148 citation statements)
references
References 21 publications
4
136
0
8
Order By: Relevance
“…In our data, dietary variety was correlated with socioeconomic status (family income and education) and religious faith, presumably because wealthier and more educated people may be more able and more motivated to vary their food intake, and religions differ in how much they restrict food consumption of their members (Van Trijp, 1994;. Within our sample of mostly elderly adults, food variety slightly decreased with age, which is in line with previous findings showing that elderly people often consume a smaller range of foods (Fanelli & Stevenhagen, 1985;Van Trijp, 1994; but see Drewnowski et al, 1997, for an increase of variety seeking with age) and that sensoryspecific satiety diminishes over the life span (Boyce & Shone, 2006;Rolls & McDermott, 1991).…”
Section: Demographic and Environmental Influencessupporting
confidence: 90%
“…In our data, dietary variety was correlated with socioeconomic status (family income and education) and religious faith, presumably because wealthier and more educated people may be more able and more motivated to vary their food intake, and religions differ in how much they restrict food consumption of their members (Van Trijp, 1994;. Within our sample of mostly elderly adults, food variety slightly decreased with age, which is in line with previous findings showing that elderly people often consume a smaller range of foods (Fanelli & Stevenhagen, 1985;Van Trijp, 1994; but see Drewnowski et al, 1997, for an increase of variety seeking with age) and that sensoryspecific satiety diminishes over the life span (Boyce & Shone, 2006;Rolls & McDermott, 1991).…”
Section: Demographic and Environmental Influencessupporting
confidence: 90%
“…15 Individuals with decreased taste sensitivity present difficulties in enjoying the taste of food, which can in some cases result in a reduction of diet and an underweight condition. 16 Population aging presents political, social and economic challenges, as Brazil currently has a lower rate of population growth and is undergoing a significant increase in its elderly population. In this context, the purpose of this study was to compare the taste sensitivity of adults with that of elderly persons and relate gustatory levels to nutritional status, smoking and alcohol consumption.…”
Section: Introductionmentioning
confidence: 99%
“…Much of the overall flavour sensation of food is produced by food stimulating the retronasal olfactory receptors. Therefore, what is often labelled as a loss of taste is, in fact, due to decline in olfactory receptors (3,4) . Fukunaga et al (5) demonstrated significant age-associated deterioration in taste discrimination between sweet, salty, sour and bitter but not somatic sensations.…”
Section: Anorexia Of Ageingmentioning
confidence: 99%